LEGAL CONSTRUCTION FOR SETTLEMENT OF SPATIAL PLANNING DISPUTES AFTER THE LAW NO.11 OF 2020 ABOUT JOB CREATION APPLIED - Sardjana Orba Manullang; Viorizza Suciani Putri; Yessy Kusumadewi; Esti Ningrum (Legal Standing : Jurnal Ilmu Hukum, 2023)
Based on experts' observations, in Indonesia, there are many phenomena of structural disputes in the use of space, namely disputes caused by policies and or decisions of public officials, both at the central and regional levels, which cause many victims in society and impact a very wide area. Before the birth of the Job Creation Law, Law Number 26 of 2007 concerning Spatial Planning regulated spatial disputes and their resolution. Still, the arrangements were unclear and often led to confusion with the mechanism for resolving spatial use violations through administrative/criminal sanctions. This study examines the Legal Construction of Spatial Planning Dispute Resolution After the Job Creation Law was enacted. The research is normative legal research with a statutory approach taken from secondary and tertiary data, which is then analyzed  . And will be analyzed by descriptive-analytical methods. The results of the study show that at the time the Job Creation Law was issued, legal reconstruction was carried out by clarifying the rules regarding spatial planning disputes, which consisted of (1) Categorizing spatial planning disputes as one of the instruments for controlling spatial use, (2) clarifying the identification of spatial planning disputes, (3) clarifies the subject and object of spatial planning disputes, (4) clarifies the mechanism for resolving spatial planning disputes and (5) clarifies the authority of each Central and Regional government.